2021
DOI: 10.3389/fpls.2021.731664
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Painting Provides Insights Into the Genome Structure and Evolution of Sugarcane

Abstract: The genus Saccharum is composed of species with high polyploidy and highly varied chromosome numbers, laying a challenge for uncovering its genomic structure and evolution. We developed a chromosome 2 painting (CP2) probe by designing oligonucleotides covering chromosome 2 of Saccharum spontaneum (2n = 8x = 64). Fluorescence in situ hybridization (FISH) using this CP2 probe revealed six types of ploidies from twenty S. spontaneum clones, including 6x, 8x, 10x, 11x, 12x, and 13x clones. The finding of S. sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The obtained results lead to a hypothesized that this was an assembly error in the current genome assembly. To confirm this hypothesis, we conducted dual-probe FISH using the chromosome 7-specific probe Ss7 ( Meng et al, 2021 ) and the Se1C692 probe. FISH results showed clear monospot signals from the centromeres of all eight chr7 homologous chromosomes ( Supplementary Figure 3 ), indicating that the Se1C692 copies were concentrated in a region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results lead to a hypothesized that this was an assembly error in the current genome assembly. To confirm this hypothesis, we conducted dual-probe FISH using the chromosome 7-specific probe Ss7 ( Meng et al, 2021 ) and the Se1C692 probe. FISH results showed clear monospot signals from the centromeres of all eight chr7 homologous chromosomes ( Supplementary Figure 3 ), indicating that the Se1C692 copies were concentrated in a region.…”
Section: Resultsmentioning
confidence: 99%
“…Saccharum spontaneum shows the highest level of genetic diversity in the Saccharum genus ( Panje and Babu, 1960 ; Irvine, 1999 ; Mary et al, 2006 ) with ploidies from 6x to 13x ( Meng et al, 2021 ). In order to study how centromeric repeats evolved along with genomic ploidy change in S. spontaneum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most advanced FISH-based approach in plants is chromosome painting (CP), which permits the selective visualization of entire chromosomes or their specific segments during mitosis as well the interphase [49][50][51][52][53][54]. The wide use of this technique for humans and mammals to determine the involvement of specific chromosomes in the formation of micronuclei showed that they preferentially comprise particular chromosomes that are related to the chromatin organization [55].…”
Section: Fluorescence In Situ Hybridization Serves To Understand the ...mentioning
confidence: 99%
“…Nevertheless, technical issues still exist and contigs cannot be assembled across centromeres or large heterochromatic blocks [ 8 , 9 , 10 ]. The fluorescence in situ hybridization (FISH) technique should therefore be applied to build a physical chromosome map in several map-poor species before starting the genome project, in order to investigate biological evolutionary constraints in genome structure [ 11 , 12 , 13 ]. It is also necessary to integrate technologies for whole-sequence data with molecular cytogenetics in so-called ‘chromosomics’ [ 14 ].…”
Section: Introductionmentioning
confidence: 99%